The reflection of corrupted government on poverty: Iraq case - Imad Ibrahim Ali Al-Sultan; Jasni Sabri; Wajdi Anwar Mardan (2015)
Corruption, best defined in relation to official government employees is the dishonesty or fraudulent conduct by those official civil servants empowered, typically involving bribery and non-legalized commission, the action of making citizens, morally depraved or the country of being so accrual of corrupt, acting to create environment or culture of corruption. Government policies can revert to be cruel on people than to be working on initiatives to eradicate poverty. The abuse of authority by violation of legally established barriers instead of override limitations to sustain development is the trend of corruption. Iraq, one of the most influential and important Arab state before the illegal invasion and occupation by the American and allied troops in 2003, was the first Arab country succeeded to eradicate poverty and in the Arab world in the eighties of the previous century. The practices and planning of all successive governments alleged by the occupier was to promote for reemerging of poverty on all levels. The paper discusses the ways and means for reducing poverty and stand against the insults, violation of law and constitutional contexts to overwhelm poverty in the society with attempt to find solutions to fight these violations and reduce poverty and corruption.